Fungsi Majelis Kehormatan Notaris Dalam Memberikan Perlindungan Hukum Terhadap Notaris Yang Tersangkut Kasus Pidana - Harseptian, Alvendo Maulana Malik; Shara, Made Cinthya Puspita (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
The purpose of this research is to find out and analyze the regulation of the function of the Notary Honorary Council in providing legal protection for the Notary Office and the concept of legal protection for the Notary Office in the future. The method used in this study is by using a normative juridical method in which an assessment of the applicable laws and regulations is carried out. The approach used is legislation, because the writer examines the rule of law. The results of this study indicate that the function of the Notary Honorary Council is in providing legal protection for the position of a notary to examine notaries and/or minutes of deeds or notary protocols using guidelines or references in carrying out their duties and authorities. The implementation of the duties and powers of the Notary Honorary Council in order to maintain the dignity of the notary's office is by cooperating with the Notary Honorary Council to determine the crime of criminalizing the position of a notary.